The Language of Shame in Cyber Discourse: A Critical Discourse Analysis of Gendered Moral Policing on X Media - Istiqomah, Istiqomah; Sastia, May; Salsabila, Elfa; Rangkuti, Rahmadsyah (Fakultas Ilmu Budaya, Universitas Jambi, 2025)
Cyber Discourse Analysis (CDA), which analyzes how language constructs and maintains power relations in online communication, enables us to study gendered moral policing on the internet. This research aims to provide linguistic evidence of how moral judgment and gender discrimination are realized in public reaction to Erika Carlina's pregnancy scandal on the social media site X. A qualitative descriptive approach, theorized by Fairclough's (1995) three-dimensional CDA model and supported by Van Dijk's (2015) discourse theory and Cameron's (2012) verbal hygiene theory, is employed. The research demonstrates that male respondents employ rational and evaluative language with a consideration of responsibility and social norms, while female respondents use emotional and corrective language that demonstrates internalized patriarchal ideology. The findings show that online discussion is an electronic extension of classical moral control, whereby the discourse of shame is employed as a communal tool of gendered judgment and social control in Indonesian society. Abstrak Analisis Wacana Siber (Cyber Discourse Analysis/CDA), yang menelaah bagaimana bahasa membangun dan mempertahankan relasi kuasa dalam komunikasi daring, memungkinkan penelitian terhadap praktik gendered moral policing atau pengawasan moral berbasis gender di internet. Penelitian ini bertujuan memberikan bukti linguistik mengenai bagaimana penilaian moral dan diskriminasi gender direalisasikan dalam reaksi publik terhadap skandal kehamilan Erika Carlina di media sosial X. Pendekatan yang digunakan adalah deskriptif kualitatif, dengan kerangka teori Analisis Wacana Kritis tiga dimensi dari Fairclough (1995), serta didukung oleh teori wacana Van Dijk (2015) dan teori verbal hygiene dari Cameron (2012). Hasil penelitian menunjukkan bahwa responden laki-laki cenderung menggunakan bahasa yang rasional dan evaluatif dengan mempertimbangkan tanggung jawab serta norma sosial, sedangkan responden perempuan menampilkan bahasa yang emosional dan korektif yang merepresentasikan internalisasi ideologi patriarki. Temuan ini mengungkap bahwa diskusi daring merupakan perpanjangan elektronik dari praktik kontrol moral klasik, di mana wacana malu digunakan sebagai alat komunal untuk menghakimi dan mengontrol perilaku berbasis gender dalam masyarakat Indonesia